Personal knowledge and information management practices of life sciences research students in Pakistan - Saleem, Qurat Ul Ain; Ameen, Kanwal; Ashiq, Murtaza (Malaysian Journal of Library and Information Science, 2021)
The study investigated personal knowledge and information management (PKIM) practices of life sciences research students and also compared their PKIM practices based on gender and research programme. The study employed survey reserach design in which questionnaire was used to collect data. All MPhil. and PhD. life sciences research students at the University of the Punjab, Lahore, Pakistan were sampled. Altogether 196 questionnaires were distributed and 114 were successfully returned with a response rate of 58 percent. The findings are presented based on the five aspects of PKIM practices of research students: (a) gathering and searching; (b) organising, keeping and securing; (c) selecting and evaluating; and (d) spreading and sharing; and (e) creating, analyzing, and presenting. The findings revealed that research student were exceptionally confident about their PKIM practices. The research students also acclaimed that they were gaining information literacy skills in practising PKIM. The PKIM practices validated in the study may help educators to design training programmes for research students in Pakistan. This study recommends library and information science researchers to investigate PKIM practices on larger scales with different populations as the idea needs more exploration to thoroughly understand the academic research environment.